Digital Agroclimatic Plot: An open-field laboratory where technology and agriculture come together to transform farming - Barrios, Camilo; Amaya, Alejandra; Arce, Daniela (2025)
The Digital Agroclimatic Plot, located at the Campus Las Américas of the Alliance Bioversity and CIAT in Palmira, Colombia, is an experimental space that integrates Internet of Things (IoT) solutions, soil monitoring sensors, multispectral drones, high-resolution satellite imagery (PlanetScope), and real-time data visualization platforms, enabled through satellite connectivity (such as Starlink). This infrastructure allows for continuous and precise monitoring of key variables related to crops, soil, and climate, such as pH, NPK, temperature, moisture, electrical conductivity, and water table levels, through data transmission networks like LoRaWAN.